2018
DOI: 10.31014/aior.1994.01.01.5
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Descriptive Cross Sectional Study About Knowledge Levels of Drug Resistant Tuberculosis Among the Residents of Port Elizabeth, Eastern Cape Province, South Africa

Abstract: The Journal of Health and Medical Sciences is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…More than half of the respondents were females (52.50%) and single (54.50%).The results also show that the majority (58%) of the participants earned R 4 999 ($357) and less per month. More than a quarter of the respondents had primary education (37.50%) and tertiary education (30.75%) [1] (Table 1).…”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than half of the respondents were females (52.50%) and single (54.50%).The results also show that the majority (58%) of the participants earned R 4 999 ($357) and less per month. More than a quarter of the respondents had primary education (37.50%) and tertiary education (30.75%) [1] (Table 1).…”
Section: Research Resultsmentioning
confidence: 99%
“…Table 2 shows that more than a quarter respondents revealed that television and radio (34.25%) and television radio and internet (30.25%) were their main sources of Drug Resistant TB information, whereas, only (14%) mentioned HCW and teachers as their source of Drug Resistant TB information [1].…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MDR-TB is defined as TB where there is in-vitro resistance to both isoniazid and rifampicin. XDR-TB is MDR-TB with additional in-vitro resistance to any fluoroquinolone and any of the three, second line injectable anti-TB drugs (T. E. Fana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%